FIGURATIVE LANGUAGE USED IN TAYLOR SWIFT’S ALBUM “FOLKLORE” - Rizal Taufik; Sri Supiah Cahyati (IKIP Siliwangi, 2022)
This research aims to explore types of figurative language found in Taylor Swift’s album and elaborate their meanings. The data source is taken from 9 (nine) songs by an American female singer, Taylor Swift. This study's main theory was adopted from the figurative language theory of Knickerbocker and Reninger (1963). The method used in this research is descriptive qualitative method. It begins with selecting several figurative sentences from nine song lyrics, then analyzed all. After analyzing, the authors recorded the related data. The results revealed that there are eleven kinds of figurative languages found out of the twelve or the total of the figurative language theory namely simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, allegory, paradox, overstatement, and irony. Keywords: Figurative Language, Song, Album